Tri-chromatic white-light emission from a single-phase Ca9Sc(PO4)7:Eu2+, Tb3+, Mn2+ phosphor for LED applications. Issue 39 (16th September 2015) - Jiang, Lihong; Pang, Ran; Li, Da; Sun, Wenzhi; Jia, Yonglei; Li, Haifeng; Fu, Jipeng; Li, Chengyu; Zhang, Su
Abstract : A wide range color-tunable tri-chromatic Ca9 Sc(PO4 )7 :Eu 2+, Tb 3+, Mn 2+ w-LED phosphor was obtained based on the efficient Eu 2+ to Tb 3+ and Eu 2+ to Mn 2+ energy transfer processes. Abstract : A series of single-phase Ca9 Sc(PO4 )7 :Eu 2+, Tb 3+, Mn 2+ phosphors for UV excitations were synthesized by a high-temperature solid-state reaction. Energy transfer from Eu 2+ → Tb 3+ and Eu 2+ → Mn 2+ in a Ca9 Sc(PO4 )7 sample is a feasible route to realize color-tunable emission because Ca9 Sc(PO4 )7 single-doped Eu 2+ /Tb 3+ /Mn 2+ emit blue, green and red light, respectively. Most of the white light region in the CIE chromaticity diagram has been realized in Ca9 Sc(PO4 )7 :Eu 2+, Tb 3+, Mn 2+ phosphors. Warm white light including the points of (0.337, 0.331), (0.353, 0.355) and (0.358, 0.327) close to day light (0.33, 0.33) with CCT of 5285 K, 4719 K and 4333 K is obtained, respectively.